PROFILE OF IMMUNIZATION PRACTICE BY GENERAL PRACTITIONERS AND PEDIATRICIANS IN PRIVATE SETTING - Soedjatmiko, Soedjatmiko; Gunardi, Hartono; Satari, Hindra Irawan; Singgih, Adrian Himawan; Yolanda, Natharina (Majalah Kedokteran Bandung, 2017)
Basic immunization coverage in Indonesia in 2013 was still low (59.2%) (IBHS, 2013). Physicians? attitude and practice were among the determinant factors of a successful immunization program. This survey aimed to describe general practitioner?s (GP) and pediatrician?s attitude towards immunization and its coverage  in private practices. This cross-sectional study was performed by distributing questionnaires consisting of 5 items on opinion and 10 items on immunization practices to 100 respondents in November 2014. Completed questionnaires were obtained from 29 GPs and 65 pediatricians. Most respondents considered that the Expanded Program in Immunization vaccine should be given. First dose of hepatitis B vaccine was mostly given in the first 12 hours after birth (90% GPs and 74% pediatricians). Oral polio vaccine was mostly given shortly before hospital discharge (65% of GPs and 81% pediatricians) while the DTwP-HB-Hib vaccine were given by 27% of GPs and 21% of pediatricians to >75% patients. Pneumococcal, rotavirus, hepatitis A, typhoid, and influenza vaccines were provided by less than 25% GPs and pediatricians, except for the influenza vaccine which was provided by 31% pediatricians. MMR vaccine was given to >75% patients by 16% of GPs and 29% of pediatricians. This pilot survey of immunization practice in private setting might be the first study in Indonesia that this can be considered as a preliminary report of immunization in private setting. Further studies need to be done, especially regarding problems in immunization in private practices. Key words: Attitude, general practitioners, immunization practice, private setting, pediatriciansGambaran Praktek Imunisasi Dokter Umum dan Dokter Spesialis Anak di Praktek SwastaRiset Kesehatan Dasar 2013 melaporkan bahwa cakupan imunisasi Indonesia masih rendah (59,2%). Sikap dan praktik imunisasi dokter merupakan salah satu faktor penentu keberhasilan. Tujuan penelitian ini mengetahui sikap dokter dan cakupan imunisasi di praktik swasta. Penelitian potong lintang dilakukan dengan menyebarkan kuesioner tentang sikap dan praktik imunisasi kepada responden, yaitu 29 dokter umum (DU) dan 65 dokter spesialis anak (DA) pada bulan November 2014. Mayoritas responden berpendapat bahwa vaksin program pengembangan imunisasi harus diberikan. Vaksin hepatitis B dosis I mayoritas diberikan dalam 12 jam setelah lahir (90% oleh DU dan 74% oleh DA). Vaksin polio oral mayoritas diberikan sebelum pulang perawatan (65% oleh DU dan 81% oleh DA), Vaksin DTwP-HB-Hib diberikan oleh 27% DU dan 21% DA kepada ?75% pasien. Penggunaan vaksin pneumokokus, rotavirus, hepatitis A, tifoid dan influenza pada >75% pasien adalah kurang dari 25%, kecuali vaksin influenza, yaitu 31% digunakan oleh DA. Pemberian vaksin MMR pada >75% pasien dilakukan oleh 16% DU dan 29% DA.  Penelitian imunisasi pada praktik swasta ini mungkin  merupakan laporan yang pertama dipublikasi di Indonesia. Penelitian lebih lanjut diperlukan untuk mengetahui hambatan imunisasi di praktik swasta.Kata kunci: Cakupan imunisasi, dokter,  imunisasi, praktik, spesialis